A live birth from vitrified‐warmed oocytes in a Philadelphia chromosome‐positive acute lymphoid leukemia patient 5 years following allogenic bone marrow transplantation and after a magnitude 9.0 earthquake in Japan. (5th June 2013) - Doshida, Masakazu; Nakajo, Yukiko; Toya, Mayumi; Kyono, Koichi
Abstract: Purpose: To report a live birth from vitrified‐warmed oocytes for a Philadelphia chromosome‐positive acute lymphoid leukemia (Ph‐ALL) patient. Methods: A 20‐year‐old single woman with Ph‐ALL requested oocyte cryopreservation at a private fertility clinic using assisted reproduction technology (ART). In cases of leukemia, there is a very short time before chemotherapy, follwed shortly by total body irradiation (TBI), and although she had already received the chemotherapy, ten oocytes were vitrified and stored for 59 months before warming. Soon after the oocyte cryopreservation, she received TBI and bone marrow transplant (BMT). During the storage, a magnitude 9.0 earthquake occurred making oocyte transport necessary. The embryo transfer was planned in a hormone replacement cycle, and intracytoplasmic sperm injection (ICSI) was performed on the vitrified‐warmed oocytes. On day 3, two embryos were transferred. Results: The patient became pregnant and delivered a healthy girl after ICSI using vitrified‐warmed oocytes. Conclusions: Oocyte cryopreservation is the best option for fertility preservation of young single women with leukemia. Oncologists and gynecologists who conduct ART should cooperate to improve the quality of life of cancer patients.